Die extraterritoriale Anwendbarkeit des UN-Sozialpakts im Zeitalter der Globalisierung: Eine völkerrechtliche Untersuchung von Jurisdiktion, Umfang und Durchsetzung extraterritorialer Menschenrechtspflichten von Staaten aus dem UN-Sozialpakt - Askin, Elif (Nomos Verlagsgesellschaft mbH & Co. KG, 2024)
This open access book examines if states are bound by the ICESCR in case of domestic measures with extraterritorial effects on economic and social human rights of individuals abroad. For states to meet the challenges posed by globalisation, it addresses the circumstances under which such effects can be considered human rights infringements. The book reveals that international law rules and jurisprudence are not sufficiently equipped to deal with questions of human rights and their extraterritorial application. It develops a new approach of ‘threshold criteria’ that may trigger extraterritorial obligations of states under the ICESCR and explores their substantive scope and enforcement on the basis of case studies.